Critical role of Hyssop plant in the possible transmission of SARS-CoV-2 in contaminated human Feces and its implications for the prevention of the virus spread in sewage - Zahmatkesh, Sasan; Klemeš, Jiří Jaromír; Bokhari, Awais; Wang, Chongqing; Sillanpaa, Mika; Hasan, Mudassir; Amesho, Kassian T T (Chemosphere, 2022)
The significant issue affecting wastewater treatment is human faeces containing SARS-CoV-2. SARS-CoV-2, as a novel coronavirus, has expanded globally. While the current focus on the COVID-19 epidemic is rightly on preventing direct transmission, the risk of secondary transmission via wastewater should not be overlooked. Many researchers have demonstrated various methods and tools for preventing and declining this virus in wastewater treatment, especially for SARS-CoV-2 in human faeces. This research reports two people tested for 30 d, with written consent, at Mosa-Ebne-Jafar Hospital of Quchan, Iran, from September 1st to October 9th, 2021. The two people's conditions are the same. The Hyssop plant was used, which boosts the immune system's effectiveness and limonene, rosemary, caffeic acids and flavonoids, all biologically active compounds in this plant, cause improved breathing problems, colds, and especially for SARS-CoV-2. As a result, utilising the Hyssop plant can help in reducing SARS-CoV-2 in faeces. This plant's antioxidant properties effectively reduce SARS-CoV-2 in faeces by 30%; nevertheless, depending on the patient's condition. This plant is also beneficial for respiratory and digestive health.
Keywords: Wastewater; Faeces; Feces; Wastewater treatment; COVID-19; Respiratory and digestive; odpadní voda; Hyssopus Plant; Waste Water; feces; Humans; SARS-CoV-2; odpadní vody; lidé; Sewage; yzop; Hyssop plant